Cr‐Doped CoP Nanorod Arrays as High‐Performance Hydrogen Evolution Reaction Catalysts at High Current Density - Zhang, Lipeng; Zhang, Juntao; Fang, Jinjie; Wang, Xin‐Yu; Yin, Likun; Zhu, Wei; Zhuang, Zhongbin (Small (Weinheim an der Bergstrasse, Germany), 2021)
Developing highly efficient, low‐cost electrocatalysts with long‐time stability at high current density working conditions for hydrogen evolution reaction (HER) remains a great challenge for the large‐scale commercialization of hydrogen production from water electrolysis. Herein, the Cr‐doped CoP nanorod arrays on carbon cloth (Cr‐CoP‐NR/CC) is reported as high performance HER catalysts with overpotentials of 38 and 209 mV at the HER current densities of 10 and 500 mA cm−2, respectively, outperforming the performance of the commercial Pt/C at high current density. And its HER performance shows almost no loss after 20 h working at 500 mA cm−2. The high performance is attributed to the Cr doping, which optimizes the hydrogen binding energy of CoP and prevents its oxidation. The nanorod array structure helps the escaping of the generated hydrogen gas, which is suitable for working at high current density. The obtained Cr‐CoP‐NR/CC catalyst shows the potential to replace the costly Pt‐based HER catalysts in the water electrolyzer. Transition metal phosphides are promising catalysts for hydrogen evolution reaction (HER) but still have the gaps to the commercial noble metal catalysts. This study reports a Cr‐doping method to fabricate high‐active and high‐stability Cr‐doped CoP nanorod arrays for HER at high current density, demonstrating that charge transfer and surface Cr species contribute to the performance enhancement.